Characterization of the antagonist actions of 5-BDBD at the rat P2X4 receptor. (18th January 2019) - Coddou, Claudio; Sandoval, Rodrigo; Hevia, María José; Stojilkovic, Stanko S.
Highlights: We confirmed that 5-BDBD is a potent P2X4 receptor antagonist. The selectivity of 5-BDBD allows to discriminate between P2X4 and other P2X subtypes. 5-BDBD can be used to determine endogenous P2X4-mediated functions in the central nervous system. Abstract: P2X receptors (P2XRs) are a family of ATP-gated ionic channels that are expressed in numerous excitable and non-excitable cells. Despite the great advance on the structure and function of these receptors in the last decades, there is still lack of specific and potent antagonists for P2XRs subtypes, especially for the P2X4R. Here, we studied in detail the effect of the P2X4R antagonist 5-(3-bromophenyl)-1, 3-dihydro- 2H -benzofuro[3, 2- e ]-1, 4-diazepin-2-one (5-BDBD) on ATP-induced currents mediated by the rat P2X4R and compared its specificity among another rat P2XRs. We found that 5-BDBD is a potent P2X4R antagonist, with an IC50 of 0.75 μM when applied for 2 min prior and during ATP stimulation. Moreover, at 10 μM concentration, 5-BDBD did not affect the ATP-induced P2X2aR, P2X2bR, and P2X7R current amplitude or the pattern of receptor desensitization. However, at 10 μM concentration but not 0.75 μM 5-BDBD inhibited the P2X1R and P2X3R-gated currents by 13 and 35% respectively. Moreover, we studied the effects of 5-BDBD in long-term potentiation experiments performed in rat hippocampal slices, finding this antagonist can partially decrease LTP, a response that is believed to be mediated in part by endogenous P2X4Rs. These results indicate that 5-BDBD could be used to study the endogenous effects of the P2X4R in the central nervous system and this antagonist can discriminate between P2X4R and other P2XRs, when they are co-expressed in the same tissue.